Biophysical properties of single rotavirus particles account for the functions of protein shells in a multilayered virus - Manuel Jiménez-Zaragoza; Marina PL Yubero; Esther Martín-Forero; Jose R Castón; David Reguera; Daniel Luque; Pedro J de Pablo; Javier M Rodríguez (eLife, 2018)
The functions performed by the concentric shells of multilayered dsRNA viruses require specific protein interactions that can be directly explored through their mechanical properties. We studied the stiffness, breaking force, critical strain and mechanical fatigue of individual Triple, Double and Single layered rotavirus (RV) particles. Our results, in combination with Finite Element simulations, demonstrate that the mechanics of the external layer provides the resistance needed to counteract the stringent conditions of extracellular media. Our experiments, in combination with electrostatic analyses, reveal a strong interaction between the two outer layers and how it is suppressed by the removal of calcium ions, a key step for transcription initiation. The intermediate layer presents weak hydrophobic interactions with the inner layer that allow the assembly and favor the conformational dynamics needed for transcription. Our work shows how the biophysical properties of the three shells are finely tuned to produce an infective RV virion.